Left Behind: A Novel of The Earth's Last Days - LaHaye, Tim, 1926-2016; Jerry B. Jenkins (USA Tyndale House Publishers, 1995)
Airline captain Rayford Steele goes in search of his family and answers to how billions of people just disappeared off the face of the Earth
Keywords: Literature (3GdCOHs; General -- Fiction; Steele, Rayford (Fictitious character); Rapture (Christian eschatology) -- Fiction; Christianity -- Controversial literature -- Fiction; Christian life -- Fiction; Christian fiction